2023
DOI: 10.1001/jamapsychiatry.2023.2392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Contextual Adaptation of the Unified Protocol in Multiple Emotional Disorders in Individuals Exposed to Armed Conflict in Colombia

Abstract: ImportanceA transdiagnostic treatment, the Unified Protocol, is as effective as single diagnostic protocols in comorbid emotional disorders in clinical populations. However, its effects on posttraumatic stress disorder and other emotional disorders in individuals living in war and armed conflict contexts have not been studied.ObjectiveTo evaluate the efficacy of a cultural and contextual adaptation of the Unified Protocol (CXA-UP) on posttraumatic stress disorder, anxiety, and depression compared to waitlist c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Specifically, the UP was efficacious when translated and culturally adapted in the contexts of a randomized controlled trial for individuals from remote areas of Colombia who were exposed to violence (e.g., armed conflict) and met criteria for posttraumatic stress disorder (PTSD), anxiety, and/or depression. In contrast to previous studies with single-disorder protocols in lower income countries that yielded moderate effects without maintenance of treatment results at follow-up, this study by Castro-Camacho et al (2023) revealed significant reductions with large effect sizes in PTSD, PTSD checklist for Diagnostic and Statistical Manual of Mental Disorders, fifth edition scores: slope ( SE ), −31.12 [3.00]; p < .001; Cohen d , 0.90, depression, nine-item Patient Health Questionnaire: slope ( SE ), −11.94 [1.30]; p < .001; Cohen d , 0.77, and anxiety, Patient Health Questionnaire—anxiety: slope ( SE ), −6.52 [0.67]; p < .001; Cohen d , 0.82. Furthermore, the UP demonstrated feasibility when modified in a randomized controlled trial within an inpatient setting consisting of patients with suicidal thoughts and behaviors, in addition to low educational attainment, unemployment and homelessness (Bentley et al, 2017).…”
Section: Candidate Transdiagnostic Treatment For Rural Populations: T...mentioning
confidence: 75%
“…Specifically, the UP was efficacious when translated and culturally adapted in the contexts of a randomized controlled trial for individuals from remote areas of Colombia who were exposed to violence (e.g., armed conflict) and met criteria for posttraumatic stress disorder (PTSD), anxiety, and/or depression. In contrast to previous studies with single-disorder protocols in lower income countries that yielded moderate effects without maintenance of treatment results at follow-up, this study by Castro-Camacho et al (2023) revealed significant reductions with large effect sizes in PTSD, PTSD checklist for Diagnostic and Statistical Manual of Mental Disorders, fifth edition scores: slope ( SE ), −31.12 [3.00]; p < .001; Cohen d , 0.90, depression, nine-item Patient Health Questionnaire: slope ( SE ), −11.94 [1.30]; p < .001; Cohen d , 0.77, and anxiety, Patient Health Questionnaire—anxiety: slope ( SE ), −6.52 [0.67]; p < .001; Cohen d , 0.82. Furthermore, the UP demonstrated feasibility when modified in a randomized controlled trial within an inpatient setting consisting of patients with suicidal thoughts and behaviors, in addition to low educational attainment, unemployment and homelessness (Bentley et al, 2017).…”
Section: Candidate Transdiagnostic Treatment For Rural Populations: T...mentioning
confidence: 75%
“…This differentiation may not only manifest in divergent mean scores across MEDI dimensions but also in the elicitation of processes and symptoms specific to trauma-related disorders—a characteristic seldom encountered within a non-clinical population (Contractor et al, 2020 ). A study in Colombia examining the effects of a culturally adapted Unified Protocol on a heterogeneous clinical sample of emotional disorders demonstrated that indeed, the clinical population exhibits high scores on tests measuring symptoms associated with PTSD, particularly the PCL-5 (Castro-Camacho et al, 2023 ). Moreover, a case study also reported in this same study indicated that in vulnerable clinical populations (from low-income backgrounds), the presence of trauma is common due to typical conditions of insecurity and a history of internal armed conflict in Colombia (Castro-Camacho et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further research into the validation of the MEDI in both clinical and non-clinical populations is warranted. Recently, in Colombia, there has been a growing interest in researching the efficacy (Castro-Camacho et al, 2023 ), effectiveness (Castro-Camacho et al, 2018 , 2019 ), prevention (Castro-Camacho et al, 2022 ), and dissemination of transdiagnostic treatments (Zarate‐Guerrero et al, 2022 ). Given the transdiagnostic structure of the MEDI, having a validated version for the Colombian population would be immensely beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Para obtener detalles exhaustivos sobre las adaptaciones realizadas, se recomienda consultar el trabajo de Castro-Camacho et al (2019). Recientemente un ensayo controlado aleatorizado de la versión adaptada del PU mostró disminuciones significativas con grandes tamaños del efecto en medidas de trastorno por estrés postraumático, ansiedad, depresión y quejas somáticas que se mantuvieron a los tres meses de seguimiento (Castro-Camacho et al, 2023).…”
Section: Pu En Poblaciones Específicasunclassified